Inhibitory effects of Helicobacter pylori infection on murine autoimmune gastritis. Issue 8 (15th July 2003) - Ohana, M; Okazaki, K; Oshima, C; Kawasaki, K; Fukui, T; Tamaki, H; Matsuura, M; Asada, M; Nishi, T; Uchida, K; Uose, S; Nakase, H; et al.
Abstract : Background and aim: Long term Helicobacter pylori infection leads to atrophic gastritis but the relation between H pylori infection and autoimmune related atrophic gastritis (AIG) remains unclear. We studied the effects of H pylori infection on the pathophysiology of AIG in mice. Materials and methods: BALB/c nu/nu mice (n=40) with or without H pylori infection received splenocytes from neonatally thymectomised mice to induce AIG. Half of the mice were orally infected with H pylori prior to AIG induction. Histological findings, and local and systemic immune responses were serially evaluated. Results: Two and six months after transfer, parietal cells in uninfected mice were depleted while those in infected mice were well preserved. The degree of gland atrophy (p<0.01), hyperplasia (p<0.01), gastric pH (p<0.05), and serum gastrin levels of infected mice were significantly lower than those of uninfected mice. Serum antiparietal cell antibody levels gradually decreased in infected mice, and were significantly lower than those of uninfected mice at six months (p<0.05). Real time polymerase chain reaction studies revealed significantly higher interleukin 4 (p<0.05) and transforming growth factor β (p<0.05) gene expression in the gastric mucosa in infected mice than in uninfected mice at both two and six months after AIG induction. Conclusions: H pylori infection inhibited the development of AIG in mice. Th2-type immune responses and transforming growth factor β in the gastric microenvironment might be involved in the inhibitory effects of H pylori infection on the development of AIG, in which Th1-type responses have an important role.